An Assessment of the Genetic Parameters of Boars' Reproductive Traits - Krupa, Emil; Krupová, Zuzana; Žáková, Eliška; Bauer, Jiří; Moravčíková, Nina; Vrtková, Irena (Genes, 2023)
The aim of this study was to estimate genetic parameters for the reproductive traits of boars based on single-nucleotide polymorphism data. A total of 109,836 semen samples from 2249 boars were collected between 2010 and 2022. Five basic traits were assessed: sperm volume, sperm concentration, motility, number of abnormal sperm, and, for the first time for the local population, libido. In addition, two derived traits were assessed: total sperm count and number of functional sperm. Genetic parameters were estimated using the single-step genomic best linear unbiased prediction method (ssGBLUP). Dam and sire breeds were evaluated separately. The five basic traits were evaluated using five-trait models, while the two derived traits were evaluated using single-trait models. The heritability coefficients had lower values for all sperm quality traits with both methods. For the basic traits, the heritability ranged from 0.099 to 0.342. The greatest difference between dam and sire breeds was observed for the heritability of the sperm concentration trait (0.099 and 0.271, respectively). The heritability of the libido trait was twice as high for boars of sire breeds as it was for boars of dam breeds. The genetic parameters estimated with ssGBLUP can be used in routine genetic evaluations to improve the pig breeding process.
Keywords: sperma; spermie; Sperm Count; genomika; Phenotype; heritability; libido; zvířata; Swine; Male; počet spermií; pig; sperm characteristics; fenotyp; ssGBLUP; Semen; Spermatozoa; Animals; mužské pohlaví; Genomics; prasata